Puccinia melitenensis (Pucciniaceae), a new rust species on Campanula stevenii subsp. beauverdiana from Malatya in Turkey - Kabaktepe, Şanlı; Mutlu, Birol; Karakuş, Şükrü (Phytotaxa, 2015)
The rust fungus Puccinia melitenensis sp. nov. on Campanula stevenii subsp. beauverdiana is described from Turkey. It is compared to other Puccinia species on Campanula and illustrated in detail.